Prove the following reduction formula: integrate of (tan^(n)x) dx= (tan^(n-1)x)/(n-1) - integrate of (tan^(n-2))dx

2 Answers | Add Yours

rcmath's profile pic

rcmath | High School Teacher | (Level 1) Associate Educator

Posted on

we need to show that `inttan^n(x)dx=(tan^(n-1)(x))/(n-1)-inttan^(n-2)(x)dx`

We know that `tan^2(x)=sec^2(x)-1`

hence we can rewrite our integral in the following manner:





In order to integrate the first part let u=tan(x) then du=sec^2(x)dx

Thus the above problem becomes








mlehuzzah's profile pic

mlehuzzah | Student, Graduate | (Level 1) Associate Educator

Posted on

`int "tan"^n x dx =`

`int ("tan" ^(n-2) x) ("tan" ^2 x) dx =`

`int ("tan" ^(n-2) x) ("sec"^2 x - 1)dx = `

`int ("tan" ^(n-2) x ) "sec"^2 x dx - int "tan" ^(n-2) x dx=`

To do the first integral, use a u substitution:

`u="tan" x` `du = "sec"^2 x dx`

`int ("tan" ^(n-2) x )"sec"^2 x dx = `

`int u^(n-2) du =`

`1/(n-1) u^(n-1) =`

`1/(n-1) "tan" ^(n-1) x`

Putting the pieces together, we get the reduction formula:

`int "tan"^n x dx = 1/(n-1) "tan" ^(n-1) x - int "tan" ^(n-2) x dx`


Here is a video explaining this problem.


We’ve answered 317,777 questions. We can answer yours, too.

Ask a question